Clinical efficacy and safety of high-intensity focused ultrasound (HIFU) ablation in treatment of cesarean scar pregnancy (CSP) I and II - Yanglu Liu; Qiaozhi Yin; Fan Xu; Shuang Luo (BMC, 2022)
Abstract Objective To investigate the safety and feasibility of high intensity focused ultrasound (HIFU) ablation followed by ultrasound-guided dilation and curettage (USg-D&C) for two types patients with cesarean scar pregnancy (CSP-I and CSP-II). Materials and methods This study was a retrospective analysis of 101 CSP-I patients and 52 CSP-II patients who received HIFU ablation followed by USg-D&C from Jun 2014 to Oct 2020. The diameter of gestational sac/mass, thickness of the intervening myometrium, intraoperative blood loss, operation time, length of hospital stays, adverse effects and β-HCG level in the two groups were compared. Results All patients successfully received HIFU ablation under conscious sedation. The median total treatment time of HIFU ablation and median USg-D&C time in the CSP-I group were statistically longer than those in the CSP-II group (P < 0.05). The average intraoperative median blood loss was 39 ml in the CSP-I group and 65 ml in the CSP-II group (P < 0.05). The duration of hospitalization was 7.07 ± 1.83 days in the CSP-I group and 7.18 ± 1.72 days in the CSP-II group (P > 0.05). The average time needed for β-HCG return to normal levels was 26.08 ± 5.02. and 28.15 ± 4.99 days for CSP-I and CSP-II, respectively (P > 0.05). The percentage of adverse effects and complications was not significantly different between the two groups (P > 0.05). Conclusions HIFU ablation followed by USg-D&C was safe and effective in treating the CSP-I patients and CSP-II patients, which may be a potential noninvasive therapeutic option for patients with CSP.